Closing wedge ostectomy and medial distal tibia plate application for treatment of severe bilateral angular limb deformities in the hindlimbs of an 8‐month‐old foal. (24th March 2021) - Lindt, B.; Fürst, A. E.; Del Chicca, F.; Malbon, A.; Jackson, M. A.
Summary: This case report describes the evaluation, surgical approach and outcome of an 8‐month‐old foal with severe angular limb deformities of both metatarsophalangeal joints (MTPJ). Radiography and computed tomography (CT) were used to diagnose a windswept deformity of the hindlimbs with associated bilateral physitis. The orthopaedic surgery was planned and rehearsed using three‐dimensional (3D) bone models. A bilateral closing wedge ostectomy was performed on the distal MtIII, and 3.5 mm LCP ® medial distal tibia plates were used bilaterally for osteosynthesis. Even though convalescence was prolonged and complicated by partial unilateral implant failure and osteoarthritis (OA), reduction of the deformities was successful and resulted in a sound foal.